Evaluation of Agroecological and Economic Efficiency of Integrated Rice-Fish Farming in Lebak Swamplands - Fyka, Samsul Alam (Jurnal Bisnis Tani, 2025)
This study aims to evaluate the suitability of soil and water and its implications for the productivity and income of farmers in integrated rice-fish farming in lebak swamp land. The research was conducted in Epeesi Village, Basala Sub-district, South Konawe District, using a descriptive quantitative approach with soil and water sampling, and interviews with farmers. Laboratory test results showed that the soil was classified as moderately suitable (S2 class), with a neutral pH and high organic matter content, but had limitations in the form of low phosphorus, potassium and soil porosity. Water quality was rated good in terms of temperature and pH, but dissolved oxygen content was slightly below the ideal standard. Rice productivity was recorded at 1,176 kg/ha and combined fish production reached 232 kg/ha. The economic efficiency value (R/C ratio) of 4.07 indicates that the system is financially profitable. These findings indicate that rice-fish integration has great potential to be implemented in lebak swamplands, provided that it is accompanied by adaptive land and water management as well as policy and institutional support for farmers.